(3PcQ CSeGA HdGO eUQs
(3ChdgG (B:s
(3GSeGA GdHdGO MQa GdCda GdCYeGd GdTQbjI GdeWQjI s
(3BNQgG (B:s
(3GdCYeGd GdCWajMjI GdCYdGe s
(3GdfSNI HgG MhGTs
(3JcQQJ CjVkG JMJ Qbe (B80 (3LZQGajGs
(3dYdg bWYI ef bhGfjf GdOhGhjf dGHf eLGJi s
(3eQJH Ydi MQha GdeYLe HMSH GdeOjQjGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdLZQGajG h GdHdOGfs